Psychology : concepts and applications / Jeffrey S Nevid - Nevid, Jeffrey S.
Offering a concept-based approach, this book provides a broad view of psychology, which includes: history, methods or research, major theories and research findings, as well as applications of contemporary research to the problems and challenges faced in everyday life.